Allelic polymorphism of crtRB1 and LcyE genes related to the β-carotene content in Vietnamese traditional maize accessions, - Thanh, Nguyen Duc; Lan, Nguyen Thi; Huong, Ho Thi (Academia Journal of Biology, 2019)
Maize is the third most important food crop after wheat and rice. Maize is used as food for more than a billion people around the world and is used as animal feed, especially, poultry. The concentration of carotenoids, especially, β-carotene in maize grains, is very low. Therefore, the study of increasing the amount of provitamin A carotenoids including β-carotene is important. In maize, different alleles of crtRB1 and LcyE genes have a significant effect on β-carotene content. In this paper, we present the results of the study of allele polymorphism of these two genes related to the provitamin A carotenoid content in some traditional maize accessions collected from several regions in North and Central Highlands of Vietnam. The results showed that there were polymorphisms at the 3’ and 5’ ends of the crtRB1 and LcyE genes. Among 22 maize accessions, the proportion of favorable alleles at the 3’ end of crtRB1 gene was relatively high (5/22 = 22.73%). Similar results were obtained for alleles at 3’ end of the LcyE gene. Especially, there is an accession (Northern white gold maize) that carries favorable alleles at the 3’ ends of both crtRB1 and LcyE genes. While all investigated maize accessions did not carry favorable alleles at the 5’ end of both crtRB1 and LcyE genes. The identification of traditional maize accessions that carry favorable alleles for increasing b-carotene content opens up potential to exploit indigenous genetic resources for genetic research as well as to develop maize varieties with high β- carotene content.